Viral suppression rates in a safety-net HIV clinic in San Francisco destabilized during COVID-19 - Spinelli, Matthew A. (AIDS, 2020)
The COVID-19 pandemic is expected to hinder U.S. End the HIV Epidemic goals. We evaluated viral suppression and retention-in-care before and after telemedicine was instituted, in response to shelter-in-place mandates, in a large, urban HIV clinic. The odds of viral non-suppression were 31% higher post-shelter-in-place (95% Confidence Interval=1.08–1.53) in spite of stable retention-in-care and visit volume, with disproportionate impact on homeless individuals. Measures to counteract the effect of COVID-19 on HIV outcomes are urgently needed.